Identifikasi Jenis Kerusakan Pada Perkerasan Lentur (Studi Kasus Jalan Soekarno-Hatta Bandar Lampung) - Putri, Vidya Annisah; Diana, I Wayan; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Soekarno-Hatta Bandar Lampung road is a national road which has function as a primary arterial road. This road having wide 2 x 7,75 m with 4/2 D type of road. This research aims to determine Soekarno-Hatta Bandar Lampung pavement condition. The method used to assessment is Pavement Condition Index (PCI). Based on the result of the study, it is known pavement condition at Soekarno-Hatta Bandar lampung road is excellent 64,3 %; very good 21,4 % and good 14,3 %. Despite the overall condition of the road was still good even perfect category, but at some location the road has been damaged. Types of damage that found in this road consisting of alligator cracking 12,64 %; block cracking 4,66%; bugs 3,35 %; depressions 2,96 %; edge cracking 4,05 %; shoulder drop off 4,14 %; longitudinal cracking 8,81 %; patching 24,61 %; polished aggregate 17,18 %, potholes 3,35 %; rutting 8,76 %; slippage cracking 2,58 % and raveling 2,92 %. Keywords : road damage, pavement condition index